«Աշխարհացոյցի» բովանդակության հարցի շուրջ - Հ. Ժ. Հարությունյան (ՀՀ ԳԱԱ հրատ.)
Детальное исследование “Ашхарацуйц”-а явствует о том, что этот источник представляет собой как политическую, так и физическую карту. Исходя из сказанного, можно заключить, что “Ашхарацуйц” был написан не только Мовсесом Хоренаци, но и Ананией Ширакаци и является источником V-VII веков.The detailed study of the content of Ashkharatsuyts” proves that this is a source of both political and physical map. This leads to the reasonable conclusion that it was written not only by Khorenatsi, but by Anania Shirakatsi too. Thus, “Ashkharatsuyts” is the source of V-VII centuries.
Keywords: History; Geography; Anthropology; Recreation; Medieval History; Mathematical geography; Cartography; D History